Importance of ground-dwelling predators on controlling 'Ceratitis capitata 'in Spanish citrus orchards - Monzó, César; Sabater-Munoz, Beatriz; García, José L.; Urbaneja, Alberto; Castanera, Pedro (2017)
There is little information on the role of the predaceous ground arthropods in citrus crops in Spain. In the present work we report on the activity-density of the predominant ground predators belonging to Araneae, Dermaptera, Staphylinidae and Carabidae. Four citrus groves in Valencia (Spain) were monitored by pitfall trapping across the diagonal in each orchard from August 2003 to April 2007. For the most abundant predators within Araneae (Pardosa cribata Simon), Dermaptera (Forficula auricularia L.) and Carabidae [(Pseudophonus rufipes (DeGeer)], it was assessed the capacity to prey on the Ceratitis capitata (Wiedemann) stages that can be found on the citrus ground (third instar larvae, pupae and teneral adults). Moreover, functional response parameters against this prey were also obtained. Finally, preydetection tools (molecular markers and immuno-assays) are being developed to establish the role of those predators in the control of C. capitata under field conditions.